2013
DOI: 10.1016/j.jnci.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of abdominoperineal resection and low anterior resection in lower and middle rectal cancer

Abstract: LAR can provide comparable local control, disease free and overall survival rates compared with APR in eligible patients with lower and middle rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Colectomy, low anterior excision, or abdominoperineal resection may be performed through laparoscopic or open surgery for the patients with colorectal cancer (10,11).…”
Section: Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…Colectomy, low anterior excision, or abdominoperineal resection may be performed through laparoscopic or open surgery for the patients with colorectal cancer (10,11).…”
Section: Contextmentioning
confidence: 99%
“…Ultimately, 27 articles were found eligible (11,13,15,16, (Figure 1). All those articles were published from 2004 to 2013.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some stage III patients with inadequate lymph nodes evaluation may be incorrectly classified as stage I or II (4,10,11). N stage is the most important prognostic factor in resected lo-coregional colorectal cancer (12). Several studies have investigated the association between the number of lymph node identified and overall survival in patients with colorectal cancer (13).…”
Section: Introductionmentioning
confidence: 99%